1971
DOI: 10.1002/1097-0142(197102)27:2<304::aid-cncr2820270209>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastases in epidermoid cell carcinoma of the head and neck

Abstract: The pattern of metastases in patients who died of epidermoid cancer of the head and neck area, between 1954 and 1967, at the Veterans Administration Research Hospital, Chicago, was studied. One hundred fifty‐three patients died of epidermoid cancer of the head and neck; metastases below the clavicles were found in 46.7% of the patients. Fourteen patients, 9.1%, died of a second primary cancer; the lung and esophagus were the most common sites. Patients with distant metastases lived, on the average, 3 months lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(27 citation statements)
references
References 6 publications
1
24
1
1
Order By: Relevance
“…The most common organ of distant metastasis of oral SCC was lung and this tendency corresponded to other reports 1,[3][4][5][6][7][8][9][10] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most common organ of distant metastasis of oral SCC was lung and this tendency corresponded to other reports 1,[3][4][5][6][7][8][9][10] .…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, metastasis was examined clinically and histopathologically in patients with oral cancer in order to elucidate the factors involved in the mechanism of metastasis. The metastatic rate was reported to be from 7.5 to 57% in patients with oral SCC [3][4][5][6][7][8] . Metastasis was detected in 11.9% as a whole in this study, which was lower than the results reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other head and neck tumours, nasopharyngeal carcinoma has a higher incidence of distant metastases (O'Brien et al, 1971;Probert et al, 1974;Merino et al, 1977). Based on clinical information without autopsy, 14.9-40.5% of distant metastases have been reported for nasopharyngeal carcinoma (Perez et al, 1969;Thompson et al, 1970;Moench et al, 1972;Hoppe et al, 1976;Bedwinek et al, 1980;Mesic et al, 1981), compared with 5.3-23.6% reported for other head and neck cancers (Castigliano et al, 1954;Arons et al, 1961;Hoye et al, 1962;Rubenfeld et al, 1962;Berger & Fletcher, 1971;Probert et al, 1974;Merino et al, 1977).…”
mentioning
confidence: 99%
“…Distant metastasis is rare in life, but necropsy studies have shown a high incidence of micro-metastases outside the head and neck 8. As many as one in six patients have synchronous or metachronous carcinomas at other sites in the pharynx or tracheobronchial tree 9…”
mentioning
confidence: 99%